Diagnostic approach and significance of inducible nitric oxide positivity in human cutaneous leishmaniasis caused by leishmania tropica - Atik, Esin; Kuk, Salih; Inandi, Tacettin (Blackwell Publishing, 2007)
Aim To determine the usefulness of polymerase chain reaction (PCR) in the diagnosis of leishmaniasis and to emphasize the importance of inducible nitric oxide (iNOS). Materials and Methods Twenty-nine patients with cutaneous leishmaniasis diagnosed according to clinical criteria who live in rural areas of Antakya-Hatay/Turkey were included in this study. Twenty-five patients free of leishmaniasis were accepted as a control group. Punch biopsies and smears were obtained from lesions of the patients in the study group. Half of each punch biopsy specimen was processed in routine tissue processing. After routine tissue processing hematoxylin-eosin and iNOS immunohistochemical staining were applied. The remaining half of the biopsy specimens was studied by PCR method. INOS-positive stained macrophages were determined. Results The positive detection rates in 29 cases of cutaneous leishmaniasis (CL) were 96.5% by PCR, 86.2% by direct microscopic evaluation of biopsy and 58.6% by direct visualization of smear in this study. iNOS reaction was mildly positive in three cases, moderately positive in six cases and strongly positive in 20 cases. Conclusion iNOS yielded positive reaction in all cases but this positivity showed differences with respect to the age of the lesions or the effect of iNOS on the immune mechanism. This reveals an inverse correlation between iNOS reactivity and duration of lesion (Spearman correlation r = -0.53, P = 0.003). There was no correlation between iNOS reactivity and patient age (Spearman correlation: r = 0.13, P = 0.5). In terms of gender, there was no association with iNOS.
Keywords: Polymerase-Chain-Reaction; Major Infection; New-World; Expression; Synthase; Biopsies; Pcr